ChemInform Abstract: Oxidative Difunctionalization of 2‐Amino‐4H‐pyrans in Iodobenzene Diacetate and N‐Chlorosuccinimide: Reactivity, Mechanistic Insights, and DFT Calculations. Issue 23 (16th May 2013) - Mandha, Santhosh Reddy; Alla, Manjula; Bommena, Vittal Rao; Nanubolu, Jagadeesh Babu; Lingala, Santosh Kumar; Yarasi, Soujanya
Abstract In the presence of PhI(O‐Ac)2 and simple alcohols, 2‐aminopyrans undergo unusual geminal dialkoxylation with 1, 2‐migration of the amino group.